PEMBERIAN TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION (TENS) MENURUNKAN INTENSITAS NYERI PADA PASIEN BEDAH UROLOGI DI RUANG RAWAT INAP MARWAH RSU HAJI SURABAYA - Balmar Morangelita Nuach; Ika Yuni Widyawati; Laily Hidayati (Universitas Airlangga, 2019)
Introduction: Urology surgical is a current surgical procedure for tractus urogenitalis disease. Issue in post urology surgical is a pain. Transcutaneous electrical nerve stimulation (TENS) is one of the nursing intervention that uses low-voltage electrical current for pain relief. TENS can improve pain mechanisms and release of endorphins to reduce pain. The aims of this study was to determine the effect of TENS on pain intensity of postoperative urology surgical patient in Haji Surabaya Public Hospital.Methods: A quasy experiment with non randomized control group pre post design was used in this study. Recruting sample by purposive sampling. There were 12 samples (6 respondents as the control group and 6 respondents as the treatment group) which recruit using purposive sampling. Independent variable was TENS. Dependent variable was pain intensity. The pain was measured by Visual Analog Scale (VAS). Data were analyzed using Wilcoxon Signed Rank Test and Mann Whitney.Result: Results of this study showed that there was a significant effect of TENS on pain intensity of postoperative urology surgical patient in Haji Surabaya Public Hospital. In the treatment group Wilcoxon Signed Rank Test p=0.084 (p<0.05), while in the control group p=0.020 (p<0.05). Mann Whitney=0.003 (p<0.05).Discussion: It can be concluded that there was a significant effect of TENS on pain intensity of postoperative urology surgical patient in Haji Surabaya Public Hospital. TENS is recommended for the independent nursing intervention to reduce postoperative urology surgical pain. Based on this result can be done to further research should analyze several factors that affects pain patients after surgical urology. Variable confounding are ethnic and cultural values, stage of development, environment and individual support, the experience of surgery pain, anxiety and stress, controls complication post surgical happened, alternative medication history, drugshistory, surgical history and disease history.